A comparison between complete and incomplete cellular precipitations. (15th March 2018) - Tu, K.N.; Gusak, A.M.
Abstract: Classical cellular precipitation is an incomplete reaction, meaning not all the supersaturated solutes can be precipitated out. Consequently, the kinetic parameters such as lamellar spacing and growth velocity cannot be defined. Recently, in 3-Dimension Integrated Circuits (3D IC) microbump technology, the porous Cu3 Sn formation is a complete cellular precipitation; the kinetic parameters can be defined. This is rare and unique in phase transformations. In this letter, kinetic models of both precipitations are analyzed for a deeper understanding. Graphical abstract: Schematic diagram of cellular precipitation of porous Cu3 Sn from Cu6 Sn5 . Image 1